Existence of Maximum Entropy Problem Solution in a General N-Dimensional Case - Ruben A. Gevorgyan; Narek D. Margaryan (Изд-во НАН РА)
In the following paper, we will define conditions, which need to be satisfied in order for the maximum entropy problem applied in European call options to have a solution in a general n-dimensional case. We will also find a minimum right boundary for the price range in order to have at least one risk neutral measure satisfying the option pricing formula. The results significantly reduce the computational time of optimization algorithms used in maximum entropy problem.
Keywords: Mathematics; Algorithm